The roles of pyroxenite and peridotite in the mantle sources of oceanic basalts - Matzen, A; Wood, B; Baker, M; Stolper, E (Nature Publishing Group, 2017)
Subduction of oceanic crust generates chemical and lithological heterogeneities in the mantle. An outstanding question is the extent to which these heterogeneities contribute to subsequent magmas generated by mantle melting, but the answer differs depending on the geochemical behaviour of the elements under investigation: analyses of incompatible elements (those that preferentially concentrate into silicate melts) suggest that recycled oceanic crust is an important contributor, whereas analyses of compatible elements (those that concentrate in crystalline residues) generally suggest it is not. Recently, however, the concentrations of Mn and Ni—two elements of varying compatibility—in early-crystallizing olivines, have been used to infer that erupted magmas are mixtures of partial melts of olivine-rich mantle rocks (that is, peridotite) and of metasomatic pyroxene-rich mantle rocks (that is, pyroxenite) formed by interaction between partial melts of recycled oceanic crust and peridotite. Here, we test whether melting of peridotite alone can explain the observed trend in olivine compositions by combining new experimental data on the partitioning of Mn between olivine and silicate melt under conditions relevant to basalt petrogenesis with earlier results on Ni partitioning. We show that the observed olivine compositions are consistent with melts of fertile peridotite at various pressures—importantly, melts from metasomatic pyroxenites are not required. Thus, although recycled materials may well be present in the mantle source regions of some basalts, the Mn and Ni data can be explained without such a contribution. Furthermore, the success of modelling the Mn–Ni contents of olivine phenocrysts as low-pressure crystallization products of partial melts of peridotite over a range of pressures implies a simple new approach for constraining depths of mantle melting.